2023
DOI: 10.1001/jama.2023.21146
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis Exposure and Adverse Pregnancy Outcomes Related to Placental Function

Torri D. Metz,
Amanda A. Allshouse,
Gwendolyn A. McMillin
et al.

Abstract: ImportanceCannabis use is increasing among reproductive-age individuals and the risks associated with cannabis exposure during pregnancy remain uncertain.ObjectiveTo evaluate the association between maternal cannabis use and adverse pregnancy outcomes known to be related to placental function.Design, Setting, and ParticipantsAncillary analysis of nulliparous individuals treated at 8 US medical centers with stored urine samples and abstracted pregnancy outcome data available. Participants in the Nulliparous Pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…For our primary outcome of interest, SGA, initial analyses indicated a higher risk of SGA in PCU patients, particularly in those using cannabis at least twice a month for two or more trimesters, consistent with some prior studies. 16 However, after adjusting for confounders, including cotinine, there were no statistically significant differences in neonatal outcomes between PCU and control patients, which has also been previously demonstrated in the literature. 17 It is possible that this finding represents a type 2 error related to sample size, since the point estimate of our aRR (Table 3; aRR=1.61 [95% C.I.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…For our primary outcome of interest, SGA, initial analyses indicated a higher risk of SGA in PCU patients, particularly in those using cannabis at least twice a month for two or more trimesters, consistent with some prior studies. 16 However, after adjusting for confounders, including cotinine, there were no statistically significant differences in neonatal outcomes between PCU and control patients, which has also been previously demonstrated in the literature. 17 It is possible that this finding represents a type 2 error related to sample size, since the point estimate of our aRR (Table 3; aRR=1.61 [95% C.I.…”
Section: Discussionsupporting
confidence: 76%
“…1.08 – 2.14]) with a larger sample size. 16 Similarly, when comparing SGA rates between high PCU, low PCU, and controls, there were no significant differences once accounting for ADI. In contrast, analyses comparing SGA across PCU+c and controls demonstrated that neonates exposed to both cannabis and nicotine had significantly higher risk of SGA than both those exposed to cannabis alone and to controls, with no difference between PCU-c neonates and controls.…”
Section: Discussionmentioning
confidence: 89%
“…23 Considering the substantial increase in cannabis use among pregnant people, the risk of adverse pregnancy outcomes, and the possible effect on neurobehavioral outcomes, these results support the need to focus on treatment and avoid unnecessary punitive reporting to child protective services. 27,28…”
Section: Discussionmentioning
confidence: 99%
“…23 Considering the substantial increase in cannabis use among pregnant people, the risk of adverse pregnancy outcomes, and the possible effect on neurobehavioral outcomes, these results support the need to focus on treatment and avoid unnecessary punitive reporting to child protective services. 27,28 Limitations of this study include the absence of data to assess drug screening practices of pregnant individuals who delivered without prenatal care at our institution. We cannot fully describe clinician approach to substance use screening and treatment before implementation of universal screening.…”
Section: Discussionmentioning
confidence: 99%
“…The American College of Obstetricians and Gynecologists (ACOG) and the American Academy of Pediatrics (AAP) ( 15 ) advise against cannabis use during pregnancy because there is convincing evidence from observational studies that people who use cannabis during pregnancy are more likely to give birth to babies that are small for their gestational age and have a low birth weight ( 16 ). Specific cannabinoids present in cannabis can be effective for multiple sclerosis and chronic pain treatment ( 16 ) but it is likely that in utero exposure to cannabis may produce negative health effects ( 17 , 18 ). However, there are limitations to the conclusiveness of the current body of evidence ( 19 ).…”
Section: Introductionmentioning
confidence: 99%